Do psychosocial factors mediate the appearance of musculoskeletal symptoms? Evidence of an empirical study about the role of mental workload in computer workers - Soria-Oliver, María; López, Jorge S.; Torrano, Fermín; García González, Guillermo (PLOS ONE, 2022)
The emergence of musculoskeletal symptoms (MSSs) in computer workers is a relevant occupational health problem. This study tests a multilevel model of analysis of risk factors in the appearance of musculoskeletal pain and discomfort in computer workers that integrates indicators from different areas: temporal usage patterns, ergonomic factors, psychosocial factors, and individual variables, specifically testing the possible mediating role of the mental workload. A cross-sectional study was performed through online registration with a non-probabilistic sample of 1198 workers from Spanish organizations. The results show that mental workload has a higher association than the rest of the factors with the onset of pain and discomfort in various body areas: neck in men, neck, shoulders and upper back in women. They also support the mediation role of mental workload in the relationship between usage patterns and the appearance of musculoskeletal symptoms. The use of multilevel theoretical models that adequately consider the complexity of the relationships between the different risk factors is necessary for a better understanding and intervention on MSSs in computer workers.
Keywords: risk-factors; office workers; muscle-activity; job strain; neck pain; disorders; prevalence; users; discomfort; shoulder; WOS(2); Scopus